Thyrocarpus fujianensis (Boraginaceae; Cynoglosseae), a new species from China: evidence from morphological and molecular analyses - Ma, Liang; Chen, Xin-Yan; Chen, Yong-Bin; Zhou, Cheng-Yuan; Liu, Ming-Zhu; Chen, Shi-Pin (Phytotaxa, 2023)
We here describe and illustrate a new species, Thyrocarpus fujianensis (Boraginaceae), from Fujian Province in southern China. Morphological comparisons indicated that T. fujianensis is similar to T. sampsonii and T. glochidiatus but displays distinct differences in habitat, leaves, pedicel, calyx, corolla and fruit. Phylogenetic analysis based on the nuclear (ITS) and two plastid DNA sequences (rps16 and trnL–trnF) showed that T. fujianensis is nested within Thyrocarpus with relatively strong supporting values but only weak support as sister to T. sampsonii. The morphological and molecular evidence both support the status of T. fujianensis as a new species.